Taboo or not taboo: swearing, satire, irony, and the grotesque in the English translation of Niccolò Ammaniti's Ti prendo e ti porto via. - Maher, Brigid (Italianist, 2012)
A literary criticism of the book "Ti prendo e ti porto via," by Niccolò Ammaniti is presented. It explores the use of taboo words from a foreign language, the depiction of a social milieu that is particular on the presentation and expression among the characters. It sheds light to the role of languages particularly taboo languages and the challenges that are inherent in the translation of swearing.